(3GdfaMGJ GdjeGfjI GdQMeGfjI aj UaGJ GdPGJ GdSdeGfjIs
(3ChdgG (B:s
(3GdMeO ddg GdPj hgH dSdjeGf edckG dGjfHZj dCMO ef HYOg hLYd GdEfS hGdLf hGdhMhT hGdWjQ hGdQjM aj LfOg s
(3BNQgG (B:s
(3hJdc GdRGhjI GdePchQI JMJGL Edi YeGQI hJQeje ChdkG hKGfjkG bO VGbJ HGdLeGYI dcKQJge hRjGOJge hUdi Gddg Ydi SjOfG eMeO hYdi Bdg hUMHg hSde s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
(3GdQHGW (B(43 (3c(B) s
Keywords: (3GdJUha hGdBOGH GdTQYjIs